Simulation and design optimization of magneto rheological control valve - Samad, Zahurin; Salloom, Maher Yahya; Hawary, Ahmad Faizul (SpringerOpen, 2011)
Magneto-rheological (MR) Valve is one of the devices generally used to control the speed of Hydraulic actuator using MR fluid. The performance of valve depends on the magnetic circuit design. Present study deals with a new design of MR valve. The finite element analysis is carried out on this valve to optimize its design. The design of the magnetic circuit is accomplished by magnetic finite element software such as Finite Element Method Magnetic (FEMM). The Model dimensions of MR valve, material properties and the circuit properties of valve coil are taken into account. The results of analysis are presented in terms of magnetic strength and magnetic flux density. The valve can be operated with variable flow rate by varying the current. It is found that the current is inversely proportional to the flow rate. High current low flow rate and vice versa.